Photoperiodic regulation of diapause in linden bugs: are period and Clock genes involved? - Syrová, Z; Dolezel, D; Saumann, I; Hodková, M (Cellular and molecular life sciences, 2003)
Although photoperiodism is undoubtedly one of the most important functions of the circadian system, the role of circadian clock genes remains unclear. We compared the expression of period and Clock genes in the head of the linden bug, Pyrrhocoris apterus, kept under diapause promoting short days (SD) and diapause-preventing long days (LD), using an RNase protection assay. There was only a weak diurnal rhythm in both period and Clock mRNA under LD and no rhythm under SD. Under SD, however, the level of period mRNA was about tenfold and that of clock mRNA about twofold higher than under LD. In a mutant that does not undergo diapause, even under SD, levels of both transcripts were low in both photoperiods. The differential regulation of the levels of two clock gene transcripts in a photoperiodic mutant, demonstrated for the first time in an animal species, strongly indicates a link between photoperiod, the magnitude of clock gene expression, and developmental outputs.
Keywords: Circadian Rhythm; jaderné proteiny; Heteroptera; Animals; cirkadiánní proteiny Period; ženské pohlaví; Period Circadian Proteins; pohybová aktivita; zvířata; Motor Activity; Photoperiod; Female; Insect Proteins; hmyzí proteiny; Nuclear Proteins; fotoperioda; cirkadiánní rytmus